From Allocation to Distribution: Are Islamic Banks Effective in Managing Zakat Funds? - Maulida, Sri; Sofyan, Muhammad (Management of Zakat and Waqf Journal (MAZAWA), 2025)
The high potential of zakat funds in Indonesia makes various parties contribute to the collection process. One of them is the Islamic Commercial Bank which also has a role as a recipient and distributor of zakat funds. The purpose of this study was to determine how the effectiveness of the performance of zakat fund management in Islamic Commercial Banks. This study adopts a descriptive qualitative approach. It gathers data on the sources and utilization of zakat funds from the annual reports of ten Islamic Commercial Banks spanning the years 2019 to 2023. To assess financial performance, the study employs two ratio analyses pertinent to Sharia Commercial Bank conditions: the Activity Ratio and the Growth Ratio. This study found that the performance of the Activity Ratio, namely the zakat allocation ratio, is in a good performance position, zakat turnover with a not good performance position, and the average of days zakat outstanding ratio with not good performance results in 2023. Then for the Growth Ratio, both allocation and distribution are both at a not good performance in the final year of the study.